Management of DOAC in Patients Undergoing Planned Surgery or Invasive Procedure: Italian Federation of Centers for the Diagnosis of Thrombotic Disorders and the Surveillance of the Antithrombotic Therapies (FCSA) Position Paper - Squizzato, Alessandro; Poli, Daniela; Barcellona, Doris; Ciampa, Antonio; Grandone, Elvira; Manotti, Cesare; Moia, Marco; Toschi, Vincenzo; Tosetto, Alberto; Testa, Sophie; Scientific Reviewer Committee; Douketis, James; Kirmani, Bil; Lip, Gregory Y.H. (Thrombosis and Haemostasis, 2022)
Patients on anticoagulant treatment are constantly increasing, with an estimated prevalence in Italy of 2% of the total population. About a quarter of the anticoagulated patients require temporary cessation of direct oral anticoagulants (DOACs) or vitamin K antagonists for a planned intervention within 2 years from anticoagulation inception. Several clinical issues about DOAC interruption remain unanswered: many questions are tentatively addressed daily by thousands of physicians worldwide through an experience-based balancing of thrombotic and bleeding risks. Among possible valuable answers, the Italian Federation of Centers for the diagnosis of thrombotic disorders and the Surveillance of the Antithrombotic therapies (FCSA) proposes some experience-based suggestions and expert opinions. In particular, FCSA provides practical guidance on the following issues: (1) multiparametric assessment of thrombotic and bleeding risks based on patients' individual and surgical risk factor, (2) testing of prothrombin time, activated partial thromboplastin time, and DOAC plasma levels before surgery or invasive procedure, (3) use of heparin, (4) restarting of full-dose DOAC after high risk bleeding surgery, (5) practical nonpharmacological suggestions to manage patients perioperatively. Finally, FCSA suggests creating a multidisciplinary “anticoagulation team” with the aim to define the optimal perioperative management of anticoagulation.
Keywords: direct oral anticoagulant; surgery; FCSA